Jadilah Mahasiswa yang Jujur dan Amanah - Dheva Fadia Anjani; Hilda Siti Aryani; Rizka Amalia; Yonika Regina; Ani Nur Aeni (Universitas Negeri Malang, 2023)
Abstract: Honesty is a characteristic where a person does not lie about the facts that happened. Meanwhile, trust is a trust given to someone or attached to someone regarding the responsibilities they hold. Honest people can definitely be trusted. Currently, honesty and trust are still not implemented by students, this can be seen from student behavior such as plagiarism in writing or cheating in proof of attendance during teaching and learning activities in class. Therefore, to find out more about this problem, researchers conducted research using the extension method. The topics discussed are related to students' understanding of the nature of honesty and trustworthiness. From the responses obtained during the counseling, students gave positive responses and were well received to broaden their insight, change their thinking patterns and change bad habits for the better. Abstrak: Kejujuran adalah suatu sifat dimana seseorang tidak melakukan kebohongan terhadap fakta yang terjadi. Sedangkan amanah merupakan kepercayaan yang diberikan seseorang atau melekat pada diri seseorang mengenai tanggung jawab yang dipegang nya. Orang yang jujur pasti dapat diberikan kepercayaan. Pada saat ini kejujuran dan kepercayaan masih kurang di terapkan oleh mahasiswa, hal ini dapat dilihat dari perilaku mahasiswa seperti adanya plagiarisme menulis atau adanya kecurangan dalam bukti kehadiran ketika kegiatan belajar mengajar dikelas. Maka dari itu, untuk mengetahui lebih dalam mengenai permasalahan ini peneliti melakukan penelitian menggunakan metode penyuluhan. Topik yang dibahas berkaitan dengan pemahaman mahasiswa mengenai sifat jujur dan amanah. Dari respon yang didapat selama penyuluhan mahasiswa memberikan respon positif dan diterima dengan baik untuk menambah wawasan, merubah pola pikir dan mengubah kebiasaan buruk menjadi lebih baik.